2020
DOI: 10.3390/bs10060105
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Problem-Based Learning and Traditional Approaches in College English Classrooms: Analyzing Pedagogical Behaviors Via Classroom Observation

Abstract: In this study, we described and compared an English as a foreign language (EFL) teacher’s pedagogical behaviors in traditional and problem-based learning (PBL) classroom settings in a Chinese university. In spring 2019, we collected six 45-min videos, three in each condition, covering three modules: (a) warm-up and vocabulary, (b) essay structure, and (c) writing. The analyses of the teacher’s pedagogical behaviors and her interaction with students indicated that the instructor spent most of the instructional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…It aims to instill knowledge into learners' brains with high efficiency. For example, Tang et al [1] argue that the earlier teaching methods used in English Teaching in China were teacher-centered grammar-translation (GT) and audiolingual methods. Grammar translation methods mainly carry out grammar teaching through translation and interpretation.…”
Section: Conventional Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…It aims to instill knowledge into learners' brains with high efficiency. For example, Tang et al [1] argue that the earlier teaching methods used in English Teaching in China were teacher-centered grammar-translation (GT) and audiolingual methods. Grammar translation methods mainly carry out grammar teaching through translation and interpretation.…”
Section: Conventional Approachmentioning
confidence: 99%
“…Tang et al [1] argue that the earlier teaching methods used in English Teaching in China were teachercentered grammar-translation (GT) and audio-lingual methods. Many researchers believe both methods trade language as a skill or habit acquired through repetition and imitation.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive conflict also provides a chance for students to receive, justify, evaluate, and refine their ideas from teachers. Asking teachers questions can enhance students’ learning initiative and improve students’ class involvement [ 6 , 45 ]. Even if these questions are not helpful or disruptive, the behavior of putting forward questions is valuable [ 46 ] because it is an outcome of students’ deep thought, which can also enhance students’ innovative competence.…”
Section: Introductionmentioning
confidence: 99%
“…are an essential part of the education process" [4] (p. 12). However, recent international studies indicate lecture-based learning is still the primary applied method in the classroom in higher education [5].…”
Section: Introductionmentioning
confidence: 99%
“…As an educational method, PBL has been gaining ground and many studies point out several advantages: student satisfaction [28], ability to integrate new information into previous knowledge [29], a greater ability to transfer concepts to new problems [30], better results [31], development of various general skills [32], increasing student attitudes and interest in a STEM career [33], providing more opportunities for students' collaboration, and, thus, promoting higher-order thinking skills [5] and enhancing student achievement [34], among others. In broader studies, literature reviews and meta-analyses reported positive reactions to the methodology [35], gains in attitudes [36], and retention of knowledge for longer periods of time compared to the traditional methodology [37], increasing articulation compared to other active learning strategies [20], but not always better academic results [38].…”
Section: Introductionmentioning
confidence: 99%